Northern European Lake Survey, 1995 - Finland, Norway, Sweden, Denmark, Russian Kola, Russian Karelia, Scotland and Wales - Henriksen, A; Skjelkvale, BL; Mannio, J; Wilander, A; Harriman, R; Curtis, C; Jensen, JP; Fjeld, E; Moiseenko, T (ROYAL SWEDISH ACAD SCIENCES, 1998)
In the autumn of 1995, Finland, Norway and Sweden initiated a joint Nordic Lake Survey using standard protocols for lake selection criteria and analytical procedures. Subsequently, the project was expanded to include Denmark, Russian Kola, Russian Karelia, Scotland and Wales. The survey covers a geographic area of ca. 1 300 000 km(2); this is about 13% of Europe's total area and 28% of Europe excluding European Russia. The total number of lakes (> 0.04 km(2)) in the study area is about 155 000 and of these 5690 lakes (3.7%) were sampled in this survey. This is 3.7% of the total lake population (> 0.04 km(2)). The lake density is about 1 lake per 9 km(2), and the sampling density is 1 lake per 244 km(2). The first common evaluation of lake chemistry in northern Europe showed that the chemistry of these lakes, except those in Denmark, are characterized by low ionic strength (dilute) waters, with low concentrations of the nutrients nitrogen and phosphorus. There are general differences in the lake water chemistry between the countries, due to differences in hydrology, precipitation chemistry, hydrology, soil cover and vegetation. From western Norway, Scotland and Wales to eastern Finland and Karelia, there is a gradient from high to low precipitation (5000 to 300 mm yr(-1)) and from mountain areas with thin and patchy soils to forested areas with thick soils. These two factors are reflected in lake water chemistry with low concentrations of base cations (Ca, Mg, Na, K), alkalinity (HCO3-) and total organic carbon (TOC) in the western areas to higher concentrations in the eastern areas. An exception is high TOC levels in lakes in Scotland and Wales. Median values for base cation concentrations are three times higher in Sweden, Finland, Scotland, and Wales than in Norway, and TOC concentrations vary even more. The lakes in Denmark are influenced by a different bedrock mineralogy than in the other countries, and agricultural activities are much more intensive in their catchments. The Danish lakes generally have much higher ion concentrations and high concentrations of nitrogen and phosphorus. In Finland, Norway, Sweden, Russian Kola and Karelia, more than 50% of the lakes have low critical load (CL) values for sulfur acidity (CL < 60 meg m(-2) yr(-1)) while Scotland, Wales, and Denmark have very few lakes with low CL. The highest percentage (27%) of lakes with exceedance of critical loads for sulfur acidity (at present S-loading) is found in Norway. In Russian Kola, Sweden and Finland 17%, 9% and 9%, respectively, of the lakes are exceeded. In Scotland, critical loads for sulfur acidity are exceeded in only 1% of the total lake population, while 24% of Welsh lakes are exceeded. In total, this adds up to approximately 22 000 lakes, corresponding to 14% of the total lake population in northern Europe, where CL for sulfur acidity is exceeded.